2000
DOI: 10.1007/pl00012045
|View full text |Cite
|
Sign up to set email alerts
|

Drug concentration in lymph nodes after preoperative administration of UFT (a blend of Tegafur and uracil) for non-small-cell lung cancer

Abstract: Background. UFT a blend of uracil and Tegafur (1-[2-tetrahydrofuryl]-5 fluorouracil), molar ratio, 4 : 1 is an antitumor agent for oral administration that is presumed to maintain the concentration of 5-fluorouracil (5-FU) in tumor tissue. The concentration of 5-FU achieved with UFT in lymph node metastases has, however, not yet been examined; in this study we aimed to clarify the transfer of 5-FU to lymph node metastases in patients treated with UFT. Methods. The subjects were 21 patients with primary nonsmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…9 The higher 5-FU concentrations found in cancerous tissues after the administration of UFT can be explained as follows. 17,18 1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 The higher 5-FU concentrations found in cancerous tissues after the administration of UFT can be explained as follows. 17,18 1.…”
Section: Discussionmentioning
confidence: 97%
“…8 As a result, when UFT is given, a desirable 5-FU concentration in tumor tissues and metastatic lymph node tissues can be maintained over a long period. 9 The pathogenesis of the tumor growth inhibition induced by long-term UFT treatment is considered to be related to a progression of apoptotic induction and a reduction of mitotic activity. 10 Tanaka et al reported that the apoptotic index (AI) was useful for predicting the efficacy of postoperative adjuvant therapy using UFT in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%